Pelatihan Fungsi Eksekutif pada Para Orangtua Anak Berkebutuhan Khusus di Sekolah Pelangi Indonesia Home Schooling Yogyakarta - Triwahyuningsih, Yeni; Kondang Budiyani; Ridwan Rahmawan (Lembaga Pengembangan Kinerja Dosen, 2026)
Children with special needs require structured support, particularly in executive function domains such as attention regulation, which play a crucial role in learning and adaptive behavior. However, many parents still have limited understanding and skills in providing appropriate developmental stimulation. This community engagement program aimed to enhance parental capacity in facilitating executive function development among children with special needs at Pelangi Indonesia Homeschooling Yogyakarta. A participatory approach was applied, including needs assessment through interviews, program design, validation with educators, and structured training implementation. The intervention focused on practical attention training using visual and auditory exercises. The results showed a consistent improvement in parents’ understanding and caregiving skills, supported by significant differences between pre- and post-training scores. Observational findings also indicated more structured, consistent, and responsive parenting practices. These findings suggest that parent-based interventions are effective in strengthening executive function stimulation in home learning contexts. This program highlights the importance of empowering parents as primary agents in supporting the developmental outcomes of children with special needs.